Drivers of phytoplankton community structure change with ecosystem ontogeny during the Quaternary. (1st August 2021) - Cvetkoska, Aleksandra; Jovanovska, Elena; Hauffe, Torsten; Donders, Timme H.; Levkov, Zlatko; Van de Waal, Dedmer B.; Reed, Jane M.; Francke, Alexander; Vogel, Hendrik; Wilke, Thomas; Wagner, Bernd; Wagner-Cremer, Friederike
Abstract: Freshwater species are particularly sensitive to climate fluctuations, but little is known of their response to the large-scale environmental change that took place during the Quaternary. This is partly due to the scarcity of continuously preserved freshwater sedimentary records with orbital chronology. We use a 1.363 Ma high-resolution fossil record of planktonic diatoms from ancient Lake Ohrid to evaluate the role of global and regional versus local-scale environmental change in driving temporal community dynamics. By using a Bayesian joint species distribution model, we found that communities were mostly driven by the local-scale environment. Its effects decreased over time, becoming less important than global and regional environment at the onset of the penultimate glacial, 0.183 Ma. Global and regional control over the environment became important with successive deepening of the lake at around 1.0 Ma, and its influence remained persistent until the present. Our high-resolution data demonstrate the critical role of lake depth and its thermal dynamics in determining phytoplankton response to environmental change by influencing lake mixing, nutrient and light availability. With this study we demonstrate the relative impact of various environmental factors and their scale-dependant effect on the phytoplankton communities during the Quaternary, emphasizing the importance of not only considering climate fluctuations in driving their structure and temporal dynamics but also the local environment. Highlights: A 1.36 Ma diatom and sedimentary record from ancient Lake Ohrid. Influence and temporal change of Quaternary environments on community dynamics. Community composition shifted three times over the lake history. Diatom community dynamics were mostly driven by local-scale environment. The effects of global/regional and local environment varied over time.